Edukasi Wakaf Hijau Bagi Pelaku Usaha Kadai Kopi Dalam Mendukung Keberlanjutan Lingkungan - Nurrahmah .; Siti Walidah Mustamin; Santi .; Faiz Fauzan; Rasti .; A. Muh. Washiyyatun Hidayat; Putri Nabila; Mawar Ayu Cahyani; Huspa Arianna; Reski Ardilla Putri; Andi Nur Afiqa; Juwita Wulandari (CV. ITTC INDONESIA, 2026)
This activity explores the concept of green waqf as an Islamic philanthropic instrument supporting environmental sustainability and examines the responses of café business actors, specifically the Kopishop “Kopimu” located within the Muhammadiyah University of Makassar (Unismuh) campus environment. The objectives are to (1) assess the awareness and understanding of green waqf among Kopimu stakeholders, (2) analyze their perceptions and responses toward environmental sustainability issues, and (3) formulate potential collaborative strategies between green waqf programs and sustainable business practices. A descriptive qualitative approach was employed through educational activities, short surveys, and semi-structured discussions with Kopimu managers and employees. The findings reveal that literacy on green waqf remains low, while sustainability awareness is relatively high, driven by consumer demands and institutional academic culture. Kopimu demonstrates openness to environmental collaboration initiatives, yet emphasizes the need for clear mechanisms, institutional support, and promotional incentives. The activity concludes that green waqf has the potential to serve as a complementary sustainability instrument for Kopimu, provided that literacy and partnership platforms are strengthened.